Effects of online automated feedback and teacher-written feedback on sixth form ESL students' writing performance - N. Govindasamy, Potchelvi (2014)
The ability to write effectively is recognized as an important skill for educational, business and personal reasons in the global community (Weigle, 2002). However, writing in ESL context can be difficult for ESL students due to their diverse background and knowledge that affect their ability to construct original texts to fulfill the expectations of the audience or teacher. Through feedback to their writing and by doing multiple revisions, they learn to develop and express complex ideas clearly and effectively. This study aims to address the need for additional research on the effectiveness of different feedback modes and to improve students’ writing. The research questions of the study are: 1) what are the students’ preferred mode of feedback for essay revision after the feedback treatment, and why? Is the preference related to their experience? ; 2) to what extent does teacher-written feedback help students improve their drafts during the writing process in the aspects of task fulfillment, language and organization? ; 3) to what extent does online automated feedback help students improve their drafts during the writing process in the aspects of task fulfillment, language and organization? ; 4) what are the effects of teacher-written feedback and online automated feedback on the students’ post-treatment essays in the aspects of task fulfillment, language and organisation?, and finally, 5) how similar or different are teacher-written feedback and online automated feedback in terms of comment types and intent and their effects on students’ essay revision? This quasi-experimental study incorporated both quantitative and qualitative data collection and analysis. The counterbalanced design was used to compare the effects of two modes of feedback on students’ essays. In the study, two intact Lower Six classes formed the experimental groups, and they received teacher-written feedback and online automated feedback treatment during essay writing for eight weeks. Prior to the written feedback treatment, students answered a questionnaire and wrote a parallel essay each for pre-treatment evaluation. The first stage of the treatment was conducted for four weeks. Group A wrote two essays to receive online automated feedback for their essay drafts and they revised their drafts based on the given feedback, while Group B wrote two essays and received teacher-written feedback and revised their drafts based on it. Students wrote the Post-treatment Essays 1 at the end of stage one. In the second stage of the experiment, the experimental groups switched treatments and continued to write two more essays each for another four weeks. Students wrote the Post-treatment Essays 2, and participated in an interview at the end of stage 2. All the students’ essay drafts written during the teacher-written feedback and online automated feedback treatment, and the pre- and post-treatment essays were rated using the MUET scoring criteria in the aspects of task fulfillment, language and organization to obtain scores. The results revealed that the students preferred teacher-written feedback to online automated feedback. Both the experimental groups showed improvement in their essay writing based on both modes of feedback. The data analysis between pre-treatment and post-treatment showed that the students improved in essay writing that was measured through mean scores for the three aspects i.e., task fulfillment, language and organization and was statistically significant. The study suggests that the integration of both teacher-written feedback and online automated feedback could be an effective technique to help ESL students in the writing classroom. In other words, students will have more opportunity to write and teachers’ burden of providing feedback can be reduced by alternating teacher-written feedback and online automated feedback in the writing classroom. The idea of providing online automated feedback during the writing process in the classroom to support essay writing is an important contribution of the study to the research field.